Calcium microdomains at the immunological synapse: how ORAI channels, mitochondria and calcium pumps generate local calcium signals for efficient T-cell activation - Quintana, Ariel (Nature Publishing Group, 2011)
Cell polarization enables restriction of signalling into microdomains. Polarization of lymphocytes following formation of a mature immunological synapse (IS) is essential for calcium-dependent T-cell activation. Here, we analyse calcium microdomains at the IS with total internal reflection fluorescence microscopy. We find that the subplasmalemmal calcium signal following IS formation is sufficiently low to prevent calcium-dependent inactivation of ORAI channels. This is achieved by localizing mitochondria close to ORAI channels. Furthermore, we find that plasma membrane calcium ATPases (PMCAs) are re-distributed into areas beneath mitochondria, which prevented PMCA up-modulation and decreased calcium export locally. This nano-scale distribution—only induced following IS formation—maximizes the efficiency of calcium influx through ORAI channels while it decreases calcium clearance by PMCA, resulting in a more sustained NFAT activity and subsequent activation of T cells.